Functional state study of cardiovascular system among young boxers during special-preparatory period of the training process - Gaynullina, A. F.; Lintvarev, A. L.; Shayakhmetova, A. S. (The Russian Journal of Physical Education and Sport, 2017)
Young boxers` training loads during special-preparatory period lead to considerable functional state tension of most physiological systems in an organism, in particular, cardiovascular system. That is why, in order to correct functional state of cardiovascular system and solve the problem of the loads increase or decrease, scientists recommend estimating this index during different periods of the training process. Materials. This research work studies the peculiarities of adaptation of young boxers` main system of an organism. Research methods: scientific-methodical literature analysis and summarizing, pedagogical experiment, methodology, testing, statistical data handling. Results. During the research it was revealed that the mean values of blood pressure among young boxers were within the range of normal values in terms of different heart rate. However, short-term physical loads lead to negative levels of cardiovascular system ("bad", "below the average") working capacity among 41,6% of sportsmen from the control group and among 33,4% of boxers from the experimental group. Conclusion. The revealed peculiarities of the functional state of an organism among young boxers at special-preparatory stage of the yearly training cycle revealed the necessity to use the sessions of audiovisual stimulation, directed at internal reserves of organism activation in order to fulfill physiological functions rehabilitation and development.